The Influence Of Marketing Strategies, Product Knowledge, And Halal Literacy On Consumer Decisions To Buy Halal Products In Sitio Tio Hilir Village - Aprena Siregar (Integrasi: Jurnal Studi Islam dan Humaniora, 2023)
The aim of this research is to analyze the simultaneous influence of marketing strategy, product knowledge and halal literacy on consumers' decisions to buy halal products in Sitio Tio Hilir Village. The research approach in this thesis is a quantitative approach and the data used is primary data. The results of the research show that there is a partial influence of marketing strategy on consumers' decisions to buy halal products in Sitio Tio Hilir Village. It is known that the t-count value of the marketing strategy variable is 3.587 which compared to 1.66216, so 3.587 1.66216 which means that the marketing strategy variable has a real influence (significant) with the consumer decision variable to buy halal products. There is no partial influence of product knowledge on consumers' decisions to buy halal products in Sitio Tio Hilir Village. It is known that the t value of the product knowledge variable is 0.343 which is compared to the t table of 1.66216, so 0.343 1.66216 which means the product knowledge variable does not have a real (significant) influence. ) with the consumer decision variable to buy halal products. There is a partial influence of halal literacy on consumers' decisions to buy halal products in Sitio Tio Hilir Village. It is known that the t-count value of the halal literacy variable is 6,440 which is compared to 1.66216, so 6,440 1.66216, which means the halal literacy variable has a real (significant) influence on the variable consumer decisions to buy halal products. There is a simultaneous influence of marketing strategy, product knowledge and halal literacy on consumers' decisions to buy halal products in Sitio Tio Hilir Village. This is known from the value of Fcount = 186,454 which is compared to Ftable of 3.10, so 186,454 3.10, which means the variables marketing strategy, product knowledge and Halal literacy simultaneously has a real (significant) relationship or positive influence on consumer decision variables to buy halal products in Sitio Tio Hilir Village.